Fatores de ocorrência da raiva humana e canina em Minas Gerais, 1999-2007. - Cristiana Ferreira Jardim de Miranda (2007)
In order to identify the factors of the occurrence of rabies in Minas Gerais, from 1999 to 2007, took place an ecological study followed a sample survey in the area identified as a priority to check such factors. The criteria used for determining the area of study were notification of cases of canine and human rabies transmitted by dogs, rates vaccine deemed appropriate by official bodies, low human development index and contiguousness geographical location. The results revealed a underestimate the canine population in municipalities of small and medium size, which have roofs vaccine over 150% of the official estimate. It was identified as an area of greater risk to rabies the northeast region of the state. 636 questionnaires were used in 32 counties, and 60% in urban areas. No correlation was obtained between low immunizationcoverage by the official estimate and positive notification of canine rabies. The factors that most influenced the occurrence of human and canine rabies were living in rural areas, contact with other species potentially transmitting, inadequate vaccination, high percentage of dogs semidomiciled and / or loose, low Human Development Index (HDI) in the region and difficulties of access to humane treatment. Minas Gerais shows a change in the epidemiological profile of rabies, which passes from urban to rural, needing a new order in the measures monitoring foraggravates it.